ANALYSIS OF FACTORS INFLUENCING CONTINUANCE INTENTION OF DIGITAL BANK USERS IN JABODETABEK: A STUDY ON USERS OF JENIUS, NEOBANK, DIGIBANK, AND TMRW APPLICATIONS - Stephani Elmanta Ratri; Tanty Oktavia (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2026)
The rapid development of digital technology has accelerated the transformation of the banking industry, particularly through the emergence of digital banking applications that enable customers to conduct financial transactions more efficiently and conveniently. This study aims to analyze the factors influencing the continuance intention of digital banking users by examining the roles of perceived ease of use, perceived usefulness, customer service quality, perceived security, and perceived risk in shaping customer satisfaction and customer trust. This research employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to active users of several digital banking applications. The analysis results indicate that perceived ease of use and customer service quality play important roles in increasing customer satisfaction. In addition, perceived risk is identified as a crucial factor in shaping customer trust toward digital banking services. Furthermore, customer satisfaction is found to be a major determinant in encouraging users to continue using digital banking applications, while customer trust also contributes positively to the intention to maintain long-term usage. The structural model demonstrates strong explanatory capability in explaining users’ continuance intention. These findings highlight that improving user experience, strengthening service quality, and managing security and risk effectively are essential strategies for digital banking providers to maintain customer satisfaction, build trust, and encourage sustainable usage of digital banking services in Indonesia.